Fundamentals of Error Theory Applications in Decision Making - Guo, Kaizhong; Liu, Shiyong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a tool for generic readers and graduates who are interested or majoring in systems engineering, decision science, management science, and project management to sharpen their system thinking skills, equipping them with a multiangle perspective, and offering them broader view to understand the complex socioeconomic system in which we are embedded. It systematically investigates the root causes and mechanisms that generate errors through the use of fuzzy set theory, systems science, logic and set theory, and decision science - an area that has rarely been explored in literature. The topics covered include classic error set, fuzzy error set, multivariate error set, error function, identification of errors, error systems, error logic, error matrix, and practical application of error theory in a sewage project.
Brief Introduction of Error Theory -- Error Set -- Error Function -- Identiﬁcation of Error -- Error Systems -- Error Logic -- Application of Error Theory -- Glossary.
Keywords: Computational intelligence; Econometrics; Artificial intelligence; Computational Intelligence; Quantitative Economics; Artificial Intelligence